Agglomeration effects and informal firms in the internal structure of cities. Issue 80 (28th August 2019) - Dominguez, Andres
Abstract : Purpose: This paper aims to estimate the effect of agglomeration on the probability of being an informal firm in Cali, Colombia. Informal firms produce legal goods but do not comply with official regulations. This issue is relevant because, similar to other developing countries, the informal sector in Colombia employs more than 50 per cent of the workforce. The results of this study demonstrate that one standard deviation increase in agglomeration reduces by 52 per cent the probability of being informal. Results are consistent with the idea that informal firms benefit less from agglomeration because of legal restrictions that block the relationship with formal firms. Design/methodology/approach: The objective of the present paper is to estimate the effect of agglomeration on the probability that a firm – given a location – chooses to be informal. The authors deal with endogeneity issues by using soil information related to earthquake risk, which reduces the height of buildings and therefore increases the cost of agglomeration. The analysis focuses on Cali, Colombia, where the informal sector employs 60 per cent of the workforce. The registration of economic activities is used as a criterion to identify informal firms, in such a way that the percentage of informal firms is 42 per cent. Findings: The authors find that the effect of agglomeration is strongly negative. The probability of being informal diminishes by 52 per cent when agglomeration increases by one standard deviation. Results in this paper shed light on how formal firms tend to be localized in high-density commercial and industrial areas, while informal firms are localized in low-density and peripheral areas where the land for production is cheaper and where they can avoid the control of authorities. Originality/value: Theory argues that spatial production externalities and commuting costs are among the main forces that shape the city's internal structure. Externalities include effects that increase firms' production, and therefore workers' income, when the size of the local economy grows. The authors now have strong evidence that firms' productivity is positively related with the volume of nearby employment. Most of the empirical findings concern firms in the formal sector and, accordingly, the literature says little about the effect of agglomeration on informal firms' location. However, this effect is crucial for developing countries where informal work is the main option for less-educated workers facing unemployment.